Comparative Analysis of Tunicate vs. Plant-Based Cellulose in Chitosan Hydrogels for Bone Regeneration - Laura Furlan; Annj Zamuner; Andrea Riccioni; Giacomo Sabbadin; Teresa Russo; Vito Gallicchio; Gabriella D’Auria; Lucia Falcigno; Lucia Manni; Loriano Ballarin; Elisabetta Schievano; Paola Brun; et al. (Gels)
A novel hydrogel scaffold for bone regeneration based on chitosan, selected for its biocompatibility, biodegradability, and antimicrobial properties, was covalently functionalized with a bioactive peptide from bone morphogenetic protein-2 (BMP-2) to guide osteoblast growth and proliferation. This study evaluates the impact of incorporating different concentrations (8, 16, or 24% wt/wt) of plant-based micro-fibrillated cellulose or tunicate nanocellulose to improve the mechanical and biological properties of peptide-grafted chitosan hydrogel matrices. While the mechanical properties of the matrices increase with increasing cellulose content, regardless of its source, the behavior of human osteoblasts used in biological tests discriminates between the two types of cellulose and shows better results (proliferation at 2 and 7 days, and mineralization) for the enrichment with tunicate cellulose.